Analysis of Key Control Points of Microbial Contamination Risk in Pork Production Processes Using a Quantitative Exposure Assessment Model - Yang, Tengteng; Zhao, Ge; Liu, Yunzhe; Wang, Lin; Gao, Yubin; Zhao, Jianmei; Liu, Na; Huang, Xiumei; Zhang, Qingqing; Liu, Junhui; Zhang, Xiyue; Wang, Junwei; et al. (Frontiers in Microbiology, 2022)
Pork is one of the most common food causing microbial foodborne diseases. Since pork after slaughtering directly enters the market, the control of microbial contamination in slaughtering processes is the key to ensure the quality and safety of pork. The contamination level of Escherichia coli, as a health-indicator bacterium, can reflect the risk level of potential pathogens. In order to assess the E. coli exposure risk of pork during slaughtering and to identify the key control points, we established E. coli quantitative exposure assessment model for swine-slaughtering processes in differently sized slaughterhouses. The model simulation data indicated the E. coli contamination pattern on surfaces of swine carcasses during slaughtering. According to the simulation data of each slaughtering process, the changes of E. coli contamination were analyzed. It was found that the number of E. coli after trimming in big and small slaughterhouses increased to the maximum value of the whole processes, which was 3.63 and 3.52 log10 CFU/100 cm2 respectively. The risk contribution of each slaughtering process to the E. coli contamination on the surface of terminal swine carcasses can be determined by correlation analysis. Because the absolute value of correlation coefficient during trimming process was maximum (-0.69), it was regarded as the most important key control point. This result can be further proved via the multilocus sequence typing of E. coli. The dominant sequence type before trimming processes was ST10. ST1434 began to appear in the trimming process and then became the dominant sequence type in the trimming and precooling processes. This model can provide a theoretical basis for microbial hygiene supervision and risk control in swine-slaughtering processes.